The impact of food crisis on performance of agribusiness firms in Malaysia - Abdurofi, Ilmas; Ismail, Mohd Mansor; Sharifuddin, Juwaidah (Australian Academy of Business and Social Sciences, 2015)
The food crisis has adversely impacted many countries in the world especially the less developed countries. But the main exporters of agricultural products like Malaysia performed extremely well during this period. Since agriculture in Malaysia is one of the main sectors that contribute to the country’s Gross Domestic Product (GDP), the impact of food crisis will be analysed in this paper through performance analysis of 40 agribusiness firms listed on Bursa Malaysia. The paper invistigates the performance of agribusiness firms in Malaysia before (2006-2008) and after (2009-2012) the food crisis using financial statements analysis such as dividend yield (DY), earning yield (EY), book to market (BM), debt equity ratio (DER) and return on asset (ROA). The secondary data on financial statements from agribusiness firms in the Malaysian Stock Exchange Statistics for the period from 2006 to 2012 were utilised. The findings show that the overall performance of agribusiness firms in terms of profitability, leverage and market ratios fluctuated between 2006 to 2012, where there are significant differences in performance between the period 2006-2008 and the period 2009-2012.The paper concludes that the performance of agribusiness firms was better in 2006-2008 and this indicates that Malaysian agribusiness firms have benefited a lot during the world food crisis.